Greywater Characteristics In Rural Areas of the Sahelian Region for Reuse Purposes: The Case of Burkina Faso - Maiga, Ynoussa; Moyenga, David; Ushijima, Ken; Sou, Mariam; Maiga, Amadou (Revue des sciences de l’eau / Journal of Water Science)

(untitled) (Université du Québec - INRS-Eau, Terre et Environnement (INRS-ETE), 2014)
AbstractThe characteristics of greywater generated in two rural areas (“Barkoundba” and “Kologoudiessé”) located in the Sahelian region in Burkina Faso were assessed through observations in selected concessions, sample collection and laboratory analyses. The study aimed at characterizing the qualitative and quantitative characteristics of greywater in order to evaluate its reuse potential for gardening in rural areas. The results showed that greywater is generated from 3 to 4 main sources with average daily productions of 8 ± 1 L•capita‑1•d‑1 in “Barkoundba” and 13 ± 3 L•capita‑1•d‑1 in Kologoudiessé”. Despite these low rates, the average quantity of greywater production varied from 67 to 344 L•concession‑1•d‑1 during the dry season. This greywater can be collected to provide additional water for irrigation in home gardens of size varying from 10 to 43 m2. Shower activity is the major contributor of greywater with up to 56% in “Barkoundba” and 70% in “Kologoudiessé”. The qualitative assessment of the greywater streams showed that every source is contaminated with chemicals and microbial pollutants at levels not suitable for direct reuse in agriculture. Therefore, it is recommended to treat the greywater before its use for irrigation purposes. Based on World Health Organization (WHO) reuse guidelines, the treatment system should be able to remove bacteria by more than 2 log units and 4 log units if restricted and unrestricted irrigation are considered respectively. Since shower greywater is directly poured onto the ground, the treatment unit should be adapted to the shower room to allow shower greywater collection, in order to collect the required quantities for gardening. A slanted soil treatment system could be investigated. Hazards of a direct reuse are discussed for soils, plants and human health on the basis of the various qualitative parameters. However, an accurate risk assessment would require further investigations with the evaluation of the interannual variability of greywater quality.